Исследование методов оценки для получения требуемого качества деталей - Москаленко, A. C. (ХНУРЭ, 2012)
In this work methods of estimation for receipt of the required details quality of are investigation. Calculation correlations for the scopes of indexes of quality are offered. The estimation algorithm of quality, allowing to automatize the process of quality estimation of castable wares, is developed.
Keywords: качество деталей